Exploring ethics : an introductory anthology - Cahn, Steven M. (Oxford University Press, 2009)
Exploring Ethics: An Introductory Anthology is a brief collection of readings in moral philosophy intended to provide a clear and definite understanding of ethics. Carefully chosen and edited by Steven Cahn for maximum accessibility, the forty selections that comprise the text are organized into three parts: Challenges to Morality, Moral Theories, and Moral Problems. The first part, Challenges to Morality, addresses the sometimes simplistic ideas students may bring to the study of morality. The second part, Moral Theories, offers a look at some of the most important and influential ethical theories, showing how a variety of thinkers have tried to answer some of philosophys most enduring questions: What differentiates right from wrong? How do we define virtue? How should we act? Finally, the third part, Moral Problems, features opposing readings on nine controversial issues, such as abortion, euthanasia, terrorism, and capital punishment. Exploring Ethics includes selections from Aristotle, Immanuel Kant, Friederich Nietzsche, James Rachels, John Rawls, and Tom Regan, among many others.All of the readings are preceded by introductions and followed by study questions prepared by the editor. With its broad and rich balance of selections, Exploring Ethics is perfect for courses in introduction to ethics and contemporary moral problems, as a stand alone text or as a companion to other books. An Instructors Manual and a Companion website accompany the text.